(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. In chemical and biological research, there is often a need for a more accurate description of individual properties of molecular objects, in particular, a comparison of their spatial and mechanical characteristics. However, scales for the quantitative description of the parameters mentioned in the title still do not exist. Methods. Quantum-chemical calculation (АМ1) of enthalpies E of formation of conformers of molecules. Results. Based on the calculated enthalpy differences ΔE, an improved algorithm was proposed and combined logarithmic scales of structural rigidity – flexibility and conformational restriction – accessibility of molecules were created. Examples of calculations for characteristic structures and their results for chain, cyclic and skeleton molecules are given. The developed algorithm demonstrates the physical nature of the mentioned parameters, exponentially related to energy and entropy. It also demonstrates connection and differences between the spatial and force characteristics of molecules. The relationship of conformational accessibility, directly related to space, with the symmetry of the molecule, and structural rigidity, related to the ability of the molecule to undergo mechanical deformations, is quantitatively related. In addition, the proposed algorithm allows to calculate the numerical indices of structural flexibility and conformational accessibility as the inverse of the values of the parameters of structural stiffness and conformational restriction. This approach greatly simplifies the perception of all four scales, because in the logarithmic dimension they are placed in pairs on one coordinate axis symmetrically to its origin. Conclusions. The proposed algorithm makes it possible to quantitatively compare the above-mentioned calculated parameters of selected molecules as a whole and their individual segments, and, if necessary, molecular complexes.